Optimization of an Ultrasound-Assisted Extraction for Simultaneous Determination of Antioxidants in Sesame with Response Surface Methodology - Dandan Wang; Liangxiao Zhang; Yueqing Xu; Xin Qi; Xuefang Wang; Xiupin Wang; Qi Zhang; Peiwu Li (MDPI AG, 2019)
Sesame is a nutritional agricultural product with medicinal properties. Accurate determination of micronutrients is important for the improvement of sesame quality and nutrition assessments. Our previous study showed that 10 antioxidants—d-homoproline, vitamin B2, coniferyl aldehyde, hesperidin, phloretin, N-acetyl-l-leucine, l-hyoscyamine, ferulic acid, 5-methoxypsoralen, and 8-methoxypsoralen—in sesame were potential characteristic nutrients in sesame. Herein, simultaneous detection of 10 different types of antioxidants was developed by using ultrasound-assisted extraction coupled with liquid chromatography-tandem mass spectrometry (UAE-LC-MS/MS) with the help of response surface methodology. The significant variables and levels were screened and optimized by combining the single factor experiment, Plackett−Burman test, and Box−Behnken design. The optimal conditions for extraction of target antioxidants in sesame were methanol solution of 75.0%, liquid-to-material ratio of 20:1 (mL/g), extraction temperature of 50 °C, extraction power of 410.0 W, extraction time of 65 min. The total yield of targets was 21.74 μg/g under the optimized conditions. The mobile phase used was 0.1% formic acid in acetonitrile and 0.1% formic acid in water, and the column was a Thermo Syncronis C18 reverse phase column (100 mm × 2.1 mm, 3 μm). All targets required only one injection and could be quickly separated and assayed within 7 min. The limits of detection and limits of quantification for these 10 nutritional compounds ranged from 0.01 to 0.11 µg/kg and from 0.04 to 0.34 µg/kg, respectively. The validation results indicated that the method had reasonable linearity (R2 ≥ 0.9990), good recoveries (71.1%−118.3%), satisfactory intra-day precision (≤9.6%) and inter-day precision (≤12.9%), and negligible matrix effects (≤13.8%). This simultaneous quantification method was accurate, fast, and robust for the assessment of sesame nutrition.